Lignin-derived carbon-supported bimetallic spinel material and preparation method and application thereof

By modifying lignin and transition metal ions to form lignin-derived carbon-backed bimetal spinel material, the problem of insufficient catalytic performance of carbon-based electrocatalysts in electrolytic seawater is solved, and low overpotential and efficient catalytic decomposition of electrolytic seawater is achieved, and rich resources and low price.

CN118756195BActive Publication Date: 2025-04-25GUANGDONG UNIV OF TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410893112.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-04
Publication Date
2025-04-25
Estimated Expiration
2044-07-04

AI Technical Summary

Technical Problem

Existing carbon-based electrocatalysts have few researches in the field of electrolyzing seawater, and there is a metal ion competition reaction, making it difficult to effectively catalyze the water decomposition process.

Method used

The coordinated reaction of modified lignin and transition metal ions is formed into a lignin-derived carbon-backed bimetal spinel material. A catalyst with high electrochemical activity is prepared by hydrothermal reaction and high-temperature carbon firing, which enhances the catalytic performance.

Benefits of technology

It realizes efficient catalytic decomposition of water with low catalytic overpotential in electrolytic seawater, significantly improving the stability and catalytic activity of the catalyst, reducing costs, and effectively utilizing industrial waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118756195B_ABST
    Figure CN118756195B_ABST
Patent Text Reader

Abstract

The present invention relates to a lignin-derived carbon-supported bimetallic spinel material and a preparation method and application thereof. The present invention performs a modification design on the functional group structure of lignin by modification, and synthesizes a modified lignin ligand with a coordination function. The ligand is precisely coordinated with the transition metal ion to form a bimetallic-lignin-based precursor. Subsequently, these precursors are subjected to a hydrothermal reaction and then placed in a tubular furnace for carbonization with a nitrogen-containing compound to prepare a bimetallic complex lignin material. The present invention greatly improves the electrochemical activity of the lignin / metal complex, and the obtained lignin-derived carbon-supported bimetallic spinel material exhibits excellent activity in the electrocatalytic hydrogen evolution process of seawater, and when the electrocatalytic activity reaches 10 mA / cm 2 The overpotential required for the current density is extremely low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomass materials and electrocatalytic materials, and in particular relates to a lignin-derived carbon-supported bimetallic spinel material and a preparation method and application thereof. Background Art

[0002] As energy demand grows, the energy crisis becomes increasingly serious. In order to reduce the pollution of traditional energy to the environment, hydrogen has attracted much attention as an efficient, sustainable and clean energy. There are many ways to produce hydrogen: coal gasification, natural gas, industrial by-products, pyrolysis, biomass and electrolysis of seawater. Electrolysis of water to produce hydrogen is an ideal way, achieving zero pollution and no emissions. However, due to the preciousness of fresh water resources, direct electrolysis of seawater has gradually gained attention. Seawater accounts for 96.5% of the earth's resources and is regarded as an unlimited resource. However, the electrolysis of seawater still faces challenges, including metal ion competition reactions. Research on electrolytic water electrode catalysts has gradually matured, including phosphides, metal oxides, nitrides, etc. Carbon-based electrocatalysts have developed rapidly in the field of water electrolysis, but there are relatively few studies in the field of seawater electrolysis.

[0003] Biomass sources are diverse and extensive, with low prices and sufficient reserves. Through atomic doping, surface functionalization, defect engineering and coordination strategies, biological resources in the environment can be converted into biomass carbon-based catalysts. Such catalysts have significantly enhanced corrosion resistance and rich pore structures, which can have better performance in water electrolysis catalytic reactions. Carbon-rich biomass is carbonized and pyrolyzed to synthesize biomass carbon-based materials. This makes such solid materials have good heat resistance, chemical inertness and thermal conductivity. Lignin has many advantages. It is an important biomass in natural materials second only to cellulose. It is an important biomass in natural materials second only to cellulose. Its rich sources and high carbon content make it a high-quality carbon material precursor. Lignin and its derivatives are extremely abundant aromatic polymers in nature, and have excellent biodegradability and compatibility, and contain extremely high carbon content. And it has a wide range of applications in energy catalytic conversion, electrochemical energy storage and environmental remediation. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects and deficiencies in the prior art, thereby providing a lignin-derived carbon-supported bimetallic spinel material and its preparation method and application. First, lignin is modified to obtain modified lignin, which is then reacted with metal ions to form a precursor, and then hydrothermally charred at high temperature to obtain a lignin-derived carbon-supported bimetallic spinel material, which highlights the advantages of biomass materials and can be used as a catalyst for electrolysis of seawater. It is stable, efficient, abundant in resources and low in price. In the process of catalytic decomposition of water, the catalytic overpotential is low.

[0005] In order to solve the above technical problems, the present invention is implemented through the following technical solutions.

[0006] The first aspect of the present invention provides a method for preparing a lignin-derived carbon-supported bimetallic spinel material, comprising the following steps:

[0007] (1) modifying lignin to obtain modified lignin; the modified lignin is selected from one or more of phosphorylated modified lignin, carboxylated modified lignin, sulfonated modified lignin, and oxidative ammonolysis modified lignin;

[0008] (2) placing the modified lignin obtained in step (1) in a solvent, adding a transition metal salt solution, and stirring the mixture thoroughly to perform a coordination reaction, thereby obtaining a metal-lignin precursor;

[0009] (3) placing the metal-lignin precursor obtained in step (2) in a hydrothermal reactor for hydrothermal reaction, followed by freeze vacuum drying;

[0010] (4) The dried product is placed in a tubular furnace for high-temperature charcoal burning, followed by washing and drying.

[0011] Preferably, the lignin in step (1) is selected from one or more of enzymatic lignin, alkali lignin, sulfite lignin, and lignin sulfonate; most preferably, the lignin is selected from alkali lignin.

[0012] Preferably, the phosphorylated modified lignin in step (1) is prepared according to the following method: hydrogen phosphate and epichlorohydrin are placed in a solvent and stirred evenly to form a mixed solution, and the pH is adjusted to 9-12, and then the lignin solution is added and heated and stirred to obtain phosphorylated modified lignin.

[0013] Preferably, the solvent is selected from deionized water.

[0014] Preferably, the mass ratio of the hydrogen phosphate, epichlorohydrin and lignin is 0.2-0.7:0.1-0.16:1; more preferably, the mass ratio of the hydrogen phosphate, epichlorohydrin and lignin is 0.35-0.55:0.12-0.14:1; most preferably, the mass ratio of the hydrogen phosphate, epichlorohydrin and lignin is 0.477:0.133:1.

[0015] Preferably, the hydrogen phosphate is selected from disodium hydrogen phosphate, dipotassium hydrogen phosphate, and diammonium hydrogen phosphate; most preferably, the hydrogen phosphate is selected from disodium hydrogen phosphate.

[0016] Preferably, the pH is adjusted to 11.

[0017] Preferably, the heating and stirring temperature is 60-100°C, and the time is 1-2h; most preferably, the heating and stirring temperature is 85°C, and the time is 1.5h.

[0018] Preferably, the carboxylated modified lignin in step (1) is prepared according to the following method: adding lignin to a NaOH aqueous solution under heating and stirring, dropping a monochloroacetic acid solution and stirring to obtain a uniform solution, then heating to react to obtain a carboxylated modified lignin solution; adjusting the pH to 4-6, centrifuging to obtain a supernatant, and adding ethanol to precipitate to obtain a carboxylated modified lignin.

[0019] Preferably, the heating and stirring temperature is 40-50°C.

[0020] Preferably, the mass ratio of the lignin to the NaOH aqueous solution is 1:1-3.

[0021] Preferably, the heating reaction is carried out at a temperature of 60-80°C and for a time of 60-120 minutes.

[0022] Preferably, the pH is adjusted to 4.9-5.1.

[0023] Preferably, the oxidized ammonolysis modified lignin in step (1) is prepared according to the following method: dissolving lignin in an ammonia solution with a concentration of 1-5%, adding 30% hydrogen peroxide, and stirring at room temperature to mix evenly; then performing a hydrothermal reaction, removing the unreacted solvent after the reaction, and vacuum drying to obtain the oxidized ammonolysis lignin.

[0024] Preferably, the mass volume ratio of the lignin to the ammonia solution is 1:60-150.

[0025] It should be understood that, unless otherwise specified, the "mass to volume ratio" in the context of the present invention should be understood in a conventional manner in the art, that is, the ratio of the mass of the solid substance (in g) to the liquid volume (in mL). For example, when the "lignin to ammonia solution is 1:100", if the amount of lignin added is 1 g, the amount of ammonia solution added is 100 mL.

[0026] Preferably, the temperature of the hydrothermal reaction is 100-150° C. and the time is 60-120 min.

[0027] Preferably, the transition metal in step (2) is selected from any two of Co, Mo, Ni, Fe and Mn; more preferably, the transition metal is selected from Co and Mo.

[0028] Preferably, the transition metal salt in step (2) is selected from one or more of hydrated cobalt chloride, cobalt acetate, cobalt sulfate, cobalt nitrate, ammonium molybdate, sodium molybdate, potassium molybdate, calcium molybdate, nickel nitrate, nickel sulfate, nickel chloride, nickel bromide, ferric chloride, ferric bromide, ferric nitrate, ferric acetate, manganese nitrate, manganese chloride, and manganese sulfate; more preferably, the transition metal salt is selected from one or more of hydrated cobalt chloride, cobalt acetate, cobalt sulfate, cobalt nitrate, ammonium molybdate, sodium molybdate, potassium molybdate, and calcium molybdate; most preferably, the transition metal salt is selected from hydrated cobalt chloride and ammonium molybdate.

[0029] Preferably, the transition metal salt solution in step (2) is selected from a hydrated cobalt chloride solution and an ammonium molybdate solution, and the molar ratio of the cobalt element in the hydrated cobalt chloride solution to the molybdenum element in the ammonium molybdate solution is 0.1-10:1; most preferably, the molar ratio of the cobalt element in the hydrated cobalt chloride solution to the molybdenum element in the ammonium molybdate solution is 0.5-2:1.

[0030] Preferably, in step (2), the mass ratio of the modified lignin to hydrated cobalt chloride is 1:1-5; the mass ratio of the modified lignin to ammonium molybdate is 1:1-10.

[0031] Preferably, in step (2), the pH value may be adjusted to 8 after the coordination reaction.

[0032] Preferably, the temperature of the hydrothermal reaction in step (3) is 150-200°C, and the time is 5-12h; most preferably, the temperature of the hydrothermal reaction is 180°C, and the time is 8h.

[0033] Preferably, the temperature of the high-temperature charcoal burning in step (4) is 500-1000°C, the heating rate is 0.5-5°C / min, and the time is 1-4h; most preferably, the temperature of the high-temperature charcoal burning is 700°C, the heating rate is 5°C / min, and the time is 2h.

[0034] Preferably, the washing in step (4) is acid washing; most preferably, the washing is carried out sequentially using hydrochloric acid solution and deionized water.

[0035] Preferably, the drying temperature in step (4) is 60° C. and the drying time is 12 h.

[0036] Preferably, the high-temperature charcoal burning in step (4) is optionally carried out under a protective gas atmosphere.

[0037] Preferably, the protective gas is selected from one or more of hydrogen, argon, helium, nitrogen and carbon dioxide; most preferably, the protective gas is selected from nitrogen.

[0038] The second aspect of the present invention provides a lignin-derived carbon-supported bimetallic spinel material prepared according to the above preparation method.

[0039] The third aspect of the present invention provides the use of the lignin-derived carbon-supported bimetallic spinel material prepared according to the above preparation method in the catalytic reaction of electrolysis of seawater.

[0040] The present invention is modified by using lignin, and its functional group is modified into a modified lignin ligand with coordination function and hydrophilicity, so as to accurately coordinate with metal ions such as Co, Mo, Ni, Fe, and Mn to form a bimetallic-lignin supramolecular precursor, and the metal ions such as Co, Mo, Ni, Fe, and Mn in the lignin supramolecular are coordinated with the groups contained in the modified lignin. The bimetallic-lignin supramolecular precursor is then placed in a hydrothermal kettle for hydrothermal reaction treatment, and then placed in a tubular furnace for in-situ carbonization with a nitrogen-containing compound to prepare a lignin-derived carbon-supported bimetallic spinel material, thereby improving the electrochemical activity of the lignin / metal complex. In the present invention, during the carbonization process of the lignin / metal complex precursor, the bimetallic ions interact with the lignin molecules, which can not only form pores in situ for the lignin carbon material, but also the synergistic catalytic effect between the metals to obtain a bimetallic doped modified lignin-based spinel carbon material, and the doped site can be used as a catalytic active site, significantly enhancing its electrocatalytic performance.

[0041] Compared with the existing technology, the present invention has the following beneficial effects:

[0042] (1) The present invention performs ring-opening modification on industrial lignin and inserts functional groups with strong coordination, thereby improving its water solubility and giving it the property of strong surface coordination ability, so that it can self-assemble with metal ions in situ within a wide pH range to form a lignin / bimetallic complex with regular microstructure, effectively improving the dispersibility of the lignin's own microstructure and its ability to bind to metal ions.

[0043] (2) The present invention modifies industrial lignin and introduces some new groups. Heteroatoms in the carbon skeleton can effectively modify the surface properties of carbon, which is beneficial to its catalytic reaction.

[0044] (3) The present invention can directly utilize the waste lignin extracted from papermaking black liquor to form a highly efficient electrocatalyst through modification, self-assembly and in-situ carbonization, thereby making high-value use of industrial waste and effectively reducing the pollution to the environment caused by papermaking waste liquor discharged from the industrial papermaking industry.

[0045] (4) As a single-function OER catalyst, the present invention exhibits excellent catalytic performance for the oxygen evolution reaction in the electrolysis of seawater. 2 The overpotential required is extremely low, and the overall performance is significantly better than similar and commercial catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 Graph showing the OER test results of the lignin-derived carbon-supported Co / Mo bimetallic spinel material prepared in Examples 1-4 and a commercial RuO2 catalyst.

[0047] Figure 2 This is a graph showing the Tafel test results of the lignin-derived carbon-supported Co / Mo bimetallic spinel material prepared in Examples 1-4 and a commercial RuO2 catalyst.

[0048] Figure 3 This is a graph showing the XRD test results of the lignin-derived carbon-supported Co / Mo bimetallic spinel material prepared in Examples 1-4.

[0049] Figure 4 This is a graph showing the OER test results of the lignin-derived carbon-supported Co / Mo bimetallic spinel material prepared in Examples 1, 7, and 8 and the commercial RuO2 catalyst.

[0050] Figure 5 This is a graph showing the Tafel test results of the lignin-derived carbon-supported Co / Mo bimetallic spinel material prepared in Examples 1, 7, and 8 and a commercial RuO2 catalyst.

[0051] Figure 6 These are the XRD test results of the lignin-derived carbon-supported Co / Mo bimetallic spinel materials prepared in Examples 1, 7, and 8.

[0052] Figure 7 This is a graph showing the OER test results of the lignin-derived carbon-supported Co / Mo bimetallic spinel material prepared in Examples 1, 5, and 6 and the commercial RuO2 catalyst.

[0053] Figure 8 This is a graph showing the Tafel test results of the lignin-derived carbon-supported Co / Mo bimetallic spinel material prepared in Examples 1, 5, and 6 and a commercial RuO2 catalyst.

[0054] Fig. 9 These are the XRD test results of the lignin-derived carbon-supported Co / Mo bimetallic spinel materials prepared in Examples 1, 5, and 6.

[0055] Fig.10 This is a 10nm TEM test result of the lignin-derived carbon-supported Co / Mo bimetallic spinel material prepared in Example 1.

[0056] Fig.11 This is a 100nm TEM test result of the lignin-derived carbon-supported Co / Mo bimetallic spinel material prepared in Example 1.

[0057] Fig.12 This is the XRD pattern of the catalyst prepared in Example 9.

[0058] Fig.13 This is the XRD pattern of the catalyst prepared in Example 10.

[0059] Fig.14 This is the XRD pattern of the catalyst prepared in Example 11. DETAILED DESCRIPTION

[0060] In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail with reference to the following embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0061] Unless otherwise defined, all technical terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The technical terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or can be prepared by existing methods.

[0062] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods. The lignin used in the embodiments and comparative examples of the present invention is alkali lignin (AL) as an example. It should be understood that lignin is only used as a raw material to provide a carbon source, and its specific type has no significant effect on the properties of the finished catalyst. When other types of lignin such as enzymatic lignin, sulfite lignin, etc. are used to prepare catalysts, the obtained catalyst performance is not significantly different from that of alkali lignin, so they are not listed one by one here.

[0063] Example 1

[0064] A lignin-derived carbon-supported bimetallic spinel material, the preparation method of which comprises the following steps:

[0065] (1) Weigh 35.8 g of Na2HPO4·12H20, dissolve it in 50 g of distilled water, transfer it to a three-necked flask and heat it in a water bath to 50°C to ensure that Na2HPO4·12H20 is completely dissolved; add 10 g of cyclochloropropane dropwise to the above solution while stirring continuously, and heat the mixed solution to 85°C for reaction for 1 hour; add NaOH to adjust the pH to 11, and then add 300 g of AL solution; continue to stir and react at 85°C for 1.5 hours, and after the reaction is completed, cool it down to obtain a phosphorylated modified lignin solution.

[0066] (2) 1.0 g of the phosphorylated modified lignin solution obtained in step (1) is placed in 50 mL of pure water and stirred evenly; cobalt chloride hexahydrate (CoCl2·6H2O) and ammonium molybdate tetrahydrate ((NH4)4MoO6·4H2O) are separately placed in 50 mL of pure water and stirred evenly by magnetic force to obtain a metal salt solution, wherein the concentrations of cobalt and molybdenum in the metal salt solution are 0.12 mmol / mL, respectively; the cobalt salt solution is first added dropwise to the phosphorylated modified lignin solution, stirred for 15 minutes to form a mixed solution, and then the molybdenum salt solution is added dropwise to the mixed solution, stirred for 15 minutes to carry out coordination reaction, and NH3·H2O and HCl are used to adjust the pH to 8, and then continue stirring for 15 minutes to obtain a cobalt / molybdenum-lignin precursor.

[0067] (3) placing the cobalt / molybdenum-lignin precursor in a tetrafluoroethylene reactor and subjecting it to a hydrothermal reaction at 180° C. for 2 h; after the reaction is completed, transferring the sample to a centrifuge tube, centrifuging it at 8000 rpm for 5 min, discarding the supernatant, taking the precipitate and freeze-drying it in a vacuum, and grinding the obtained sample to obtain a cobalt / molybdenum-lignin-based supramolecular precursor.

[0068] (4) 1 g of the cobalt / molybdenum-lignin-based supramolecular precursor was placed in a tube furnace and subjected to high-temperature carbonization in a N2 atmosphere according to a thermal stabilization procedure. The high-temperature carbonization temperature was 700°C, the heating rate was 5°C / min, and the time was 2 h. After the high-temperature carbonization was completed, the product was cooled to room temperature, washed with 1 mol / L hydrochloric acid solution and deionized water, respectively, and dried at 60°C for 12 h. The scanning electron micrograph of the product is shown in FIG. Fig.10 shown.

[0069] Example 2

[0070] A lignin-derived carbon-supported bimetallic spinel material, the preparation method of which comprises the following steps:

[0071] (1) 1 g of alkali lignin (AL) was dissolved in 90 mL of 3% ammonia solution, and then 10 mL of 30% hydrogen peroxide was added, and the mixture was stirred at room temperature for 10 minutes. Then, the mixture was transferred to a hydrothermal reactor and reacted at 120°C for 90 minutes. After the reaction was completed, the mixture was cooled to room temperature. The reaction product (OAL) was subjected to rotary evaporation to remove unreacted reactants and water, and then vacuum dried and ground into powder.

[0072] (2) 1.0 g of the oxidative ammoniation modified lignin solution obtained in step (1) is placed in 50 mL of pure water and stirred evenly; cobalt chloride hexahydrate (CoCl2·6H2O) and ammonium molybdate tetrahydrate ((NH4)4MoO6·4H2O) are separately placed in 50 mL of pure water and magnetically stirred evenly to obtain a metal salt solution, wherein the concentrations of cobalt and molybdenum in the metal salt solution are 0.12 mmol / mL, respectively; the cobalt salt solution is first added dropwise to the phosphorylated modified lignin solution, stirred for 15 minutes to form a mixed solution, and then the molybdenum salt solution is added dropwise to the mixed solution, stirred for 15 minutes for coordination reaction, and NH3·H2O and HCl are used to adjust the pH to 8, and then continue stirring for 15 minutes to obtain a cobalt / molybdenum-lignin precursor.

[0073] (3) placing the cobalt / molybdenum-lignin precursor in a tetrafluoroethylene reactor and subjecting it to a hydrothermal reaction at 180° C. for 2 h; after the reaction is completed, transferring the sample to a centrifuge tube, centrifuging it at 8000 rpm for 5 min, discarding the supernatant, taking the precipitate and freeze-drying it in a vacuum, and grinding the obtained sample to obtain a cobalt / molybdenum-lignin-based supramolecular precursor.

[0074] (4) 1 g of the cobalt / molybdenum-lignin-based supramolecular precursor was placed in a tubular furnace and subjected to high-temperature charcoal calcination in a N2 atmosphere according to a thermal stabilization procedure. The high-temperature charcoal calcination temperature was 700°C, the heating rate was 5°C / min, and the time was 2 h. After the high-temperature charcoal calcination was completed, the product was cooled to room temperature, washed with 1 mol / L hydrochloric acid solution and deionized water, respectively, and dried at 60°C for 12 h.

[0075] Example 3

[0076] A lignin-derived carbon-supported bimetallic spinel material, the preparation method of which comprises the following steps:

[0077] (1) Under stirring at 45°C, 10g of enzymatic lignin was added to 20g of NaOH (20%) aqueous solution, and then 6g of monochloroacetic acid was dissolved in 10g of deionized water. After the enzymatic lignin was completely dissolved, it was slowly dripped into the above lignin solution, stirred for 20 minutes, and a uniform solution was obtained. The temperature was raised to 70°C and the reaction was continued for 90 minutes to obtain a carboxylated modified enzymatic lignin solution. After the solution was cooled to room temperature, the pH of the solution was adjusted to 5.0±0.1 with 1mol / L hydrochloric acid, and the upper layer of liquid was taken at a speed of 10000rpm for 10 minutes, and ethanol was added to precipitate to obtain carboxylated modified enzymatic lignin.

[0078] (2) 1.0 g of the carboxylated modified lignin solution obtained in step (1) is placed in 50 mL of pure water and stirred evenly; cobalt chloride hexahydrate (CoCl2·6H2O) and ammonium molybdate tetrahydrate ((NH4)4MoO6·4H2O) are separately placed in 50 mL of pure water and magnetically stirred evenly to obtain a metal salt solution, wherein the concentrations of cobalt and molybdenum in the metal salt solution are 0.12 mmol / mL, respectively; the cobalt salt solution is first added dropwise to the phosphorylated modified lignin solution, stirred for 15 minutes to form a mixed solution, and then the molybdenum salt solution is added dropwise to the mixed solution, stirred for 15 minutes for coordination reaction, and NH3·H2O and HCl are used to adjust the pH to 8, and then continue stirring for 15 minutes to obtain a cobalt / molybdenum-lignin precursor.

[0079] (3) placing the cobalt / molybdenum-lignin precursor in a tetrafluoroethylene reactor and subjecting it to a hydrothermal reaction at 180° C. for 2 h; after the reaction is completed, transferring the sample to a centrifuge tube, centrifuging it at 8000 rpm for 5 min, discarding the supernatant, taking the precipitate and freeze-drying it in a vacuum, and grinding the obtained sample to obtain a cobalt / molybdenum-lignin-based supramolecular precursor.

[0080] (4) 1 g of the cobalt / molybdenum-lignin-based supramolecular precursor was placed in a tubular furnace and subjected to high-temperature charcoal calcination in a N2 atmosphere according to a thermal stabilization procedure. The high-temperature charcoal calcination temperature was 700°C, the heating rate was 5°C / min, and the time was 2 h. After the high-temperature charcoal calcination was completed, the product was cooled to room temperature, washed with 1 mol / L hydrochloric acid solution and deionized water, respectively, and dried at 60°C for 12 h.

[0081] Example 4

[0082] A lignin-derived carbon-supported bimetallic spinel material, the preparation method of which comprises the following steps:

[0083] (1) 1.0 g of sodium lignin sulfonate was placed in 50 mL of pure water and stirred evenly to obtain a sodium lignin sulfonate solution; cobalt chloride hexahydrate (CoCl2·6H2O) and ammonium molybdate tetrahydrate ((NH4)4MoO6·4H2O) were placed in 50 mL of pure water and stirred evenly by magnetic stirring to obtain a metal salt solution, wherein the concentrations of cobalt and molybdenum in the metal salt solution were 0.12 mmol / mL, respectively; the cobalt salt solution was first added dropwise to the phosphorylated modified lignin solution, stirred for 15 min to form a mixed solution, and then the molybdenum salt solution was added dropwise to the mixed solution, stirred for 15 min to carry out coordination reaction, and NH3·H2O and HCl were used to adjust the pH to 8, and then stirred for 15 min to obtain a cobalt / molybdenum-lignin precursor.

[0084] (2) placing the cobalt / molybdenum-lignin precursor in a tetrafluoroethylene reactor and subjecting it to a hydrothermal reaction at 180° C. for 2 h; after the reaction is completed, transferring the sample to a centrifuge tube, centrifuging it at 8000 rpm for 5 min, discarding the supernatant, taking the precipitate and freeze-drying it in a vacuum, and grinding the obtained sample to obtain a cobalt / molybdenum-lignin-based supramolecular precursor.

[0085] (3) 1 g of the cobalt / molybdenum-lignin-based supramolecular precursor was placed in a tubular furnace and subjected to high-temperature charcoal calcination in a N2 atmosphere according to a thermal stabilization procedure. The high-temperature charcoal calcination temperature was 700°C, the heating rate was 5°C / min, and the time was 2 h. After the high-temperature charcoal calcination was completed, the product was cooled to room temperature, washed with 1 mol / L hydrochloric acid solution and deionized water, respectively, and dried at 60°C for 12 h.

[0086] Furthermore, by adjusting the molar ratio of cobalt chloride hexahydrate to ammonium molybdate tetrahydrate, the temperature of high-temperature charcoal burning and other parameters in the preparation process of Example 1, different lignin-derived carbon-supported Co / Mo bimetallic spinel materials were prepared. The details are shown in Table 1 below.

[0087] Table 1 Lignin-based Ru / Co bimetallic materials prepared in Examples 5-8

[0088]

[0089] Furthermore, different bimetallic materials were complexed with modified lignin using the same preparation method as in Example 1 to prepare different lignin-derived carbon-supported bimetallic spinel materials, as shown in Table 2 below.

[0090] Metal 1 Metal 2 Calcination temperature Example 9 Fe Mo 700 Example 10 Fe Ni 700 Embodiment 11 Ni La 700

[0091] Comparative Example 1

[0092] A lignin-derived carbon-supported bimetallic material, the preparation method of which comprises the following steps:

[0093] (1) Weigh 35.8 g of Na2HPO4·12H20, dissolve it in 50 g of distilled water, transfer it to a three-necked flask and heat it in a water bath to 50°C to ensure that Na2HPO4·12H20 is completely dissolved; add 10 g of cyclochloropropane dropwise to the above solution while stirring continuously, and heat the mixed solution to 85°C for reaction for 1 hour; add NaOH to adjust the pH to 11, and then add 300 g of AL solution; continue to stir and react at 85°C for 1.5 hours, and after the reaction is completed, cool it down to obtain a phosphorylated modified lignin solution.

[0094] (2) 5.0 g of the phosphorylated modified lignin solution obtained in step (1) was placed in a flask, stirred at 60° C. until it became powdery, and then placed in a N2 atmosphere for high-temperature charcoal calcination in a thermal stabilization procedure. The high-temperature charcoal calcination temperature was 400° C., the heating rate was 5° C. / min, and the time was 2 h. After the high-temperature charcoal calcination was completed, the product was cooled to room temperature.

[0095] (3) Cobalt chloride hexahydrate (CoCl2·6H2O) and ammonium molybdate tetrahydrate ((NH4)4MoO6·4H2O) were placed in 50 mL of pure water and stirred evenly by magnetic stirring to obtain a metal salt solution, wherein the concentrations of cobalt and molybdenum in the metal salt solution were 0.12 mmol / mL, respectively; the product obtained in step (2) was immersed in the metal salt solution for 12 h, and the precipitate was dried at 60° C. to obtain a cobalt / molybdenum-lignin supramolecular precursor.

[0096] (4) 1 g of the cobalt / molybdenum-lignin-based supramolecular precursor was placed in a tubular furnace and subjected to high-temperature charcoal calcination in a N2 atmosphere according to a thermal stabilization procedure. The high-temperature charcoal calcination temperature was 700°C, the heating rate was 5°C / min, and the high-temperature charcoal calcination time was 2 h. After the high-temperature charcoal calcination was completed, the product was cooled to room temperature, washed with 1 mol / L hydrochloric acid solution and deionized water, respectively, and dried at 60°C for 12 h.

[0097] Comparative Example 2

[0098] A lignin-derived carbon-supported Co single metal material, the preparation method of which comprises the following steps:

[0099] (1) Weigh 35.8 g of Na2HPO4·12H20, dissolve it in 50 g of distilled water, transfer it to a three-necked flask and heat it in a water bath to 50°C to ensure that Na2HPO4·12H20 is completely dissolved; add 10 g of cyclochloropropane dropwise to the above solution while stirring continuously, and heat the mixed solution to 85°C for reaction for 1 hour; add NaOH to adjust the pH to 11, and then add 300 g of AL solution; continue to stir and react at 85°C for 1.5 hours, and after the reaction is completed, cool it down to obtain a phosphorylated modified lignin solution.

[0100] (2) 5.0 g of the phosphorylated modified lignin solution obtained in step (1) is placed in 50 mL of pure water and stirred evenly; cobalt chloride hexahydrate (CoCl2·6H2O) is placed in 50 mL of pure water and magnetically stirred evenly to obtain a metal salt solution, wherein the concentration of cobalt element in the metal salt solution is 0.12 mmol / mL; the metal salt solution is added dropwise to the phosphorylated modified lignin solution, stirred for 15 min to form a mixed solution, and the pH is adjusted to 8 using NH3·H2O and HCl, and stirring is continued for 15 min.

[0101] (3) placing the product of step (2) in a tetrafluoroethylene reactor and subjecting it to a hydrothermal reaction at 180° C. for 8 h; after the reaction is completed, transferring the sample to a centrifuge tube, centrifuging at 8000 rpm for 5 min, discarding the supernatant, taking the precipitate and freeze-drying it in a vacuum, and grinding the obtained sample to obtain a cobalt-lignin-based supramolecular precursor.

[0102] (4) 1 g of the cobalt-lignin-based supramolecular precursor was placed in a tubular furnace and subjected to high-temperature charcoal calcination in a N2 atmosphere according to a thermal stabilization procedure. The high-temperature charcoal calcination temperature was 700°C, the heating rate was 5°C / min, and the time was 2 h. After the high-temperature charcoal calcination was completed, the product was cooled to room temperature, washed with 1 mol / L hydrochloric acid solution and deionized water, respectively, and dried at 60°C for 12 h.

[0103] Comparative Example 3

[0104] A lignin-derived carbon-supported Mo single metal material, the preparation method of which comprises the following steps:

[0105] (1) Weigh 35.8 g of Na2HPO4·12H20, dissolve it in 50 g of distilled water, transfer it to a three-necked flask and heat it in a water bath to 50°C to ensure that Na2HPO4·12H20 is completely dissolved; add 10 g of cyclochloropropane dropwise to the above solution while stirring continuously, and heat the mixed solution to 85°C for reaction for 1 hour; add NaOH to adjust the pH to 11, and then add 300 g of AL solution; continue to stir and react at 85°C for 1.5 hours, and after the reaction is completed, cool it down to obtain a phosphorylated modified lignin solution.

[0106] (2) 5.0 g of the phosphorylated modified lignin solution obtained in step (1) is placed in 50 mL of pure water and stirred evenly; ammonium molybdate tetrahydrate ((NH4)4MoO6·4H2O) is placed in 50 mL of pure water and stirred evenly by magnetic force to obtain a metal salt solution, wherein the concentration of molybdenum element in the metal salt solution is 0.12 mmol / mL; the metal salt solution is added dropwise to the phosphorylated modified lignin solution, stirred for 15 min to form a mixed solution, and the pH is adjusted to 8 using NH3·H2O and HCl, and stirring is continued for 15 min.

[0107] (3) placing the product of step (2) in a tetrafluoroethylene reactor and subjecting it to a hydrothermal reaction at 180° C. for 8 h; after the reaction is completed, transferring the sample to a centrifuge tube, centrifuging at 8000 rpm for 5 min, discarding the supernatant, taking the precipitate and freeze-drying it in a vacuum, and grinding the obtained sample to obtain a molybdenum-lignin-based supramolecular precursor.

[0108] (4) 1 g of the molybdenum-lignin-based supramolecular precursor was placed in a tubular furnace and subjected to high-temperature charcoal calcination in a N2 atmosphere according to a thermal stabilization procedure. The high-temperature charcoal calcination temperature was 700°C, the heating rate was 5°C / min, and the time was 2 h. After the high-temperature charcoal calcination was completed, the product was cooled to room temperature, washed with 1 mol / L hydrochloric acid solution and deionized water, respectively, and dried at 60°C for 12 h.

[0109] Comparative Example 4

[0110] A lignin-derived carbon-supported bimetallic material, the preparation method of which comprises the following steps:

[0111] (1) 1.0 g of AL was placed in 50 mL of pure water and stirred evenly to obtain a lignin solution; cobalt chloride hexahydrate (CoCl2·6H2O) and ammonium molybdate tetrahydrate ((NH4)4MoO6·4H2O) were placed in 50 mL of pure water and stirred evenly by magnetic stirring to obtain a metal salt solution, in which the concentrations of cobalt and molybdenum were 0.12 mmol / mL, respectively; the cobalt salt solution was first added dropwise to the lignin solution and stirred for 15 min to form a mixed solution, and then the molybdenum salt solution was added dropwise to the mixed solution and stirred for 15 min for coordination reaction, and NH3·H2O and HCl were used to adjust the pH to 8, and then stirring was continued for 15 min to obtain a cobalt / molybdenum-lignin precursor.

[0112] (2) placing the cobalt / molybdenum-lignin precursor in a tetrafluoroethylene reactor and subjecting it to a hydrothermal reaction at 180° C. for 2 h; after the reaction is completed, transferring the sample to a centrifuge tube, centrifuging it at 8000 rpm for 5 min, discarding the supernatant, taking the precipitate and freeze-drying it in a vacuum, and grinding the obtained sample to obtain a cobalt / molybdenum-lignin-based supramolecular precursor.

[0113] (3) 1 g of the cobalt / molybdenum-lignin-based supramolecular precursor was placed in a tubular furnace and subjected to high-temperature charcoal calcination in a N2 atmosphere according to a thermal stabilization procedure. The high-temperature charcoal calcination temperature was 700°C, the heating rate was 5°C / min, and the time was 2 h. After the high-temperature charcoal calcination was completed, the product was cooled to room temperature, washed with 1 mol / L hydrochloric acid solution and deionized water, respectively, and dried at 60°C for 12 h.

[0114] Verification Example 1

[0115] The lignin-derived carbon-supported Co / Mo bimetallic spinel materials prepared in Examples 1-8 were respectively taken for electrochemical performance tests to examine their catalytic performance in water electrolysis reactions. The electrochemical performance tests were carried out on a Gamry Interface 1010 electrochemical workstation, using a traditional three-electrode system, a spectrally pure graphite rod (purity 99.999%) as a counter electrode, and Hg / HgO as a reference electrode. The working electrode was made using the "drip coating method", where 4 mg of carbon material powder was added to 200 μL of 0.25% Nafion-ethanol solution and ultrasonically dispersed for 15 minutes. 50 μL of the sample dispersion was dripped onto carbon paper (0.5×0.5 mm). The resulting catalyst loading was 4.0 mg·cm -2 .

[0116] The electrochemical performance tests were carried out in 1 M KOH + 0.5 M NaCl (simulated seawater) electrolyte solution. The polarization curves were measured by linear sweep voltammetry. The oxygen evolution reaction was started at 0 V and the reaction temperature was 2 mV·s -1 The rate was scanned to 1 V. The electrocatalytic activity of the catalyst was measured in a standard three-electrode system. In order to exclude the potential gain effect of Pt on the catalyst, the auxiliary electrode was replaced with a spectroscopically pure graphite rod. In the OER test, RuO2 catalyst was used as a comparison, and the current density was 10 mA cm -2 The test results are shown in Table 2 below.

[0117] Table 2 OER test results of Examples 1-8

[0118] Tafel slope / mV / dec OER overpotential / mV Example 1 110 180 Example 2 160 220 Example 3 155 220 Example 4 150 220 Example 5 112 260 Example 6 137 230 Example 7 123 260 Example 8 150 260 <![CDATA[RuO2]]> 56 220

[0119] in Figure 1-2 , Figure 3 They are respectively the OER test result graphs and XRD graphs of the lignin-derived carbon-supported Co / Mo bimetallic spinel materials of Examples 1-4 in different modification modes and the commercial RuO2 catalyst. Figure 4-5 , Figure 6 They are respectively the OER test results and XRD diagrams of the lignin-derived carbon-supported Co / Mo bimetallic spinel materials of Examples 1 and 7-8 at different calcination temperatures and commercial RuO2 catalysts. Figure 7-8 , Fig. 9 They are respectively the OER test result graphs and XRD graphs of the lignin-derived carbon-supported Co / Mo bimetallic spinel materials of Examples 1, 5-6 and commercial RuO2 catalyst at different metal ratios. Fig.12 This is the XRD diagram of the catalyst of Example 9. It can be seen from the figure that the obtained product is Fe2Mo4O8, which is an iron-molybdenum bimetallic spinel structure. Fig.13The XRD of the catalyst obtained in Example 10 shows that the obtained material is a spinel material of ferroferric oxide, in which a small amount of iron-nickel alloy is mixed. Fig.14 This is the XRD diagram of the catalyst of Example 11. In the figure, it can be seen that the main structure is LaNiO3, which is in the form of spinel and is also doped with some La element and nickel oxide.

[0120] The results show that doping with metal Co and Mo can greatly reduce the oxygen evolution overpotential, thereby improving the electrocatalytic oxygen production performance; and the ratio of Co and Mo elements doped in the preparation process, the lignin modification method, the high-temperature charcoal burning temperature and other conditions all have a significant impact on the catalytic performance of the lignin-derived carbon-supported Co / Mo bimetallic spinel material. In general, the lignin-derived carbon-supported Co / Mo bimetallic spinel material prepared in Example 1 has a better comprehensive catalytic performance in the electrolytic water oxygen evolution reaction, which is comparable to the commercial RuO2 catalyst.

[0121] Furthermore, the materials prepared in Example 1 and Comparative Examples 1-4 were respectively subjected to the above electrochemical performance test, and the results are shown in Table 3 below.

[0122] Table 3 OER test results of Example 1 and Comparative Examples 1-4

[0123] Tafel slope / mV / dec OER overpotential / mV Example 1 110 180 Comparative Example 1 210 280 Comparative Example 2 250 370 Comparative Example 3 260 300 Comparative Example 4 370 290

[0124] It can be seen from the above results that the lignin-derived carbon-supported Co / Mo bimetallic spinel material prepared by the present invention has significantly better catalytic performance in electrolyzing seawater to produce oxygen than Co monometallic catalyst or Mo monometallic catalyst. In comparative example 1, when preparing the lignin-based bimetallic material precursor, the impregnation method is used to replace the hydrothermal method of the present invention to load Co and Mo, so that most of the product forms are presented in the form of MoO2, and the CoMo bimetallic spinel form is almost lost, resulting in the catalytic performance of the obtained material being far inferior to that of the material of the present invention; in comparative examples 2 and 3, when preparing the lignin-based monometallic material precursor, only one of the metals is used to coordinate with lignin, resulting in a poor complexing effect between the metal and lignin, and the obtained metal form is a monometallic oxide, which cannot maintain the spinel form, resulting in a catalytic performance far inferior to the catalyst material of the spinel form of the present invention, which fully proves the importance of functional groups modified into modified lignin ligands with coordination functions and hydrophilicity and bimetals for the formation of spinel form.

[0125] The spinel structure of Co2Mo3O8 (cobalt molybdenum oxide) is a special crystal structure with a cubic close-packed structure type. This can be proved by the XRD pattern, and the dispersion degree of metal particles in the TEM pattern also assisted in proving this point. In this structure, cobalt (Co) and molybdenum (Mo) ions and oxygen (O) ions are arranged in a specific ratio, forming an alternating stacking of octahedrons and tetrahedrons, forming a stable crystal structure. Cobalt and molybdenum ions are arranged alternately in the crystal structure and form octahedral and tetrahedral coordination configurations with the surrounding oxygen ions. This arrangement makes the crystal structure highly symmetrical and stable. At the same time, due to the different valence states and sizes of cobalt and molybdenum ions, they can form a stable coordination environment at specific positions in the crystal, thereby further stabilizing the spinel structure.

[0126] In general, Co2Mo3O8 has a spinel structure, which means that the cobalt, molybdenum and oxygen ions in its crystals are arranged in a specific way to form a stable octahedral and tetrahedral stacking structure, which has an important influence on its performance in applications such as catalysis. Overall, the spinel morphology has a great influence on the catalytic results. It can be seen from the XRD diagram that different temperatures, different metal ratios, etc. will affect the formation and crystallinity of the spinel results, and thus affect the catalytic performance of the catalyst.

[0127] The above specific implementation method part specifically introduces the analytical method involved in the present invention. It should be noted that the above introduction is only to help those skilled in the art better understand the method and ideas of the present invention, rather than limiting the relevant content. Without departing from the principle of the present invention, those skilled in the art may also make appropriate adjustments or modifications to the present invention, and the above adjustments and modifications shall also fall within the scope of protection of the present invention.

Claims

1. A method for preparing a lignin-derived carbon-supported bimetallic spinel material, characterized in that: The steps include: (1) modifying lignin to obtain modified lignin; the modified lignin is selected from one or more of phosphorylated modified lignin, carboxylated modified lignin, sulfonated modified lignin, and oxidative ammonolysis modified lignin; (2) placing the modified lignin obtained in step (1) in a solvent, adding a cobalt salt solution and a molybdenum salt solution, and stirring them thoroughly to carry out a coordination reaction to obtain a metal-lignin precursor; the molar ratio of the cobalt element in the cobalt salt solution to the molybdenum element in the molybdenum salt solution is 1:1; (3) placing the metal-lignin precursor obtained in step (2) in a hydrothermal reactor for hydrothermal reaction, and then drying; the hydrothermal reaction temperature is 180° C. and the time is 2 h; (4) The dried product is placed in a tubular furnace for high-temperature charcoal calcination, followed by washing and drying; the high-temperature charcoal calcination temperature is 700°C, the heating rate is 5°C / min, and the insulation time is 2h.

2. The preparation method according to claim 1, characterized in that: The phosphorylated modified lignin in step (1) is prepared according to the following method: hydrogen phosphate and epichlorohydrin are placed in a solvent and stirred evenly to form a mixed solution, and the pH is adjusted to 9-12, and then the lignin solution is added and heated and stirred to obtain phosphorylated modified lignin; The carboxylated modified lignin in step (1) is prepared according to the following method: adding lignin to a NaOH aqueous solution under heating and stirring, dropping a monochloroacetic acid solution and stirring to obtain a uniform solution, then heating to react, to obtain a carboxylated modified lignin solution; adjusting the pH to 4-6, centrifuging to obtain a supernatant, adding ethanol to precipitate to obtain a carboxylated modified lignin; The oxidized ammonium modified lignin in step (1) is prepared according to the following method: dissolving lignin in an ammonia solution with a concentration of 1-5%, adding 30% hydrogen peroxide, and stirring and mixing at room temperature; then performing a hydrothermal reaction, removing the unreacted solvent after the reaction is completed, and vacuum drying to obtain the oxidized ammonium modified lignin.

3. The preparation method according to claim 1, characterized in that: The lignin in step (1) is selected from one or more of enzymatic lignin, alkali lignin, sulfite lignin, and lignin sulfonate.

4. The preparation method according to claim 1, characterized in that: The cobalt salt in step (2) is selected from one or more of hydrated cobalt chloride, cobalt acetate, cobalt sulfate, and cobalt nitrate, and the molybdenum salt is selected from one or more of ammonium molybdate, sodium molybdate, potassium molybdate, and calcium molybdate.

5. The preparation method according to claim 1, characterized in that: The high-temperature charcoal burning in step (4) is carried out under a protective gas atmosphere.

6. The lignin-derived carbon-supported bimetallic spinel material prepared according to the preparation method according to any one of claims 1 to 5.

7. Use of the lignin-derived carbon-supported bimetallic spinel material prepared according to the preparation method according to any one of claims 1 to 5 in the catalytic reaction of electrolysis of seawater.

Citation Information

Patent Citations

  • Preparation method of lignin-based bimetallic catalyst and application of lignin-based bimetallic catalyst in hydrogen evolution by electrolyzing water

    CN114875443A

  • Lignin-based Ru / Co bimetallic in-situ N-doped carbon material as well as preparation method and application thereof

    CN117230479A